(untitled) (Journal of Information Technologies in Education (ITE), 2008)
The methods of teaching of mathematical subjects must conform to the requirements of modern science and technique, to the necessities of society. The basic components of the system of mathematical preparation of future specialists of aviation industry are analysed in the article, for the students of the first and second courses the necessity of algorithmic approach is underlined the feature of teaching of higher mathematics at teaching from the first steps of teaching in higher educational establishment.